Hearing and exposure to music in adolescents from four schools of Córdoba, Argentina - Gaetán, Sara; Muratore, Jimena; Maggi, Ana Luz; Pérez Villalobo, Jorge alejandro; Hinalaf, María (My University, 2021)
The aims of this study are (a) to characterize the hearing of adolescents from four schools of Córdoba, Argentina, through the analysis of conventional and extended highfrequency audiometric thresholds and otoacoustic emissions (OAEs) and (b) to analyze the association between the mentioned hearing tests and exposure to music.
Keywords: Audiometric thresholds; otoacoustic emissions; Adolescents